Implementing teaching in English at the University of Algiers 3: Case study of the special section of Information and Communication Sciences Faculty (2024/2025) - MEBTOUCHE, Nawel (Journal of Human Sciences, 2025)
This study aims to shed light on the recent reforms that affected the Algerian education sector. It’s about the adoption of the English language in teaching starting from the academic year 2022-2023 through the decision dated September 28th 2022.In application of this decision, the Faculty of Media and Communication at the University of Algiers3 has opened to new students the possibility of preparing a Bachelor’s degree in Information and Communication Sciences in English. The second batch of 79 students enrolled in the academic year 2024/2025 was studied. A descriptive-analytical approach and a questionnaire were used as a tool for data collection. The study found that the reasons that prompted the students to pursue a Bachelor’s degree in English were the opening of international job opportunities, and the possibility of working in foreign intercontinental companies. This experiment also allowed foreign students to practice their studies at the University of Algiers 3.